1997
DOI: 10.1038/sj.onc.1201152
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of the hepatocyte growth factor (HGF) gene by the Sp family of transcription factors

Abstract: In this study, we have localized an enhancer element in the 5'-¯anking region of the HGF gene promoter and have identi®ed its functional transcriptional factors. Through transient transfection of NIH3T3 ®broblast cells and gel mobility shift assays, the functional binding site was localized to a short region (7318 to 7303 bp from the transcription start site) which has a CTCCC sequence. This motif is also conserved in the human HGF promoter and acts as a binding site for the Sp family of transcription factors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 40 publications
(58 reference statements)
1
25
0
Order By: Relevance
“…DNase I footprinting using intact nuclei from regenerating mouse liver identi®ed several hypersensitive sites within the upstream region of the HGF promoter, one of which was mapped to a region approximately 0.3 kb from the transcription initiation site (Bell et al, 1998). Similar results were obtained when intact nuclei from NIH3T3 cells were subjected to DNase I footprinting (Jiang et al, 1997b). In vitro analysis of the HGF promoter using transient transfection of HGF-promoter constructs into NIH3T3 ®broblasts showed that a regulatory element(s) is present from 0.2 to 0.3 kb upstream of the promoter (Liu et al, 1994;Plashke-Schlutter et al, 1995).…”
supporting
confidence: 60%
See 1 more Smart Citation
“…DNase I footprinting using intact nuclei from regenerating mouse liver identi®ed several hypersensitive sites within the upstream region of the HGF promoter, one of which was mapped to a region approximately 0.3 kb from the transcription initiation site (Bell et al, 1998). Similar results were obtained when intact nuclei from NIH3T3 cells were subjected to DNase I footprinting (Jiang et al, 1997b). In vitro analysis of the HGF promoter using transient transfection of HGF-promoter constructs into NIH3T3 ®broblasts showed that a regulatory element(s) is present from 0.2 to 0.3 kb upstream of the promoter (Liu et al, 1994;Plashke-Schlutter et al, 1995).…”
supporting
confidence: 60%
“…Toward this, our laboratory as well as others have shown that several potential transcriptional regulatory elements are present in the 5'-¯anking region of the HGF gene promoter (Aravamundan et al, 1993;Liu et al, 1994;Okajima et al, 1993;Plaschke-Schlutter et al, 1995). Our previous studies demonstrated that several transcription factors, including estrogen receptor (ER) and chicken ovalbumin upstream promoter transcription factor (COUP-TF) (Jiang et al, 1997a), C/EBP (Jiang and Zarnegar, 1997), and Sp1 (Jiang et al, 1997b), bind to the HGF promoter region and regulate its activity.…”
mentioning
confidence: 96%
“…This inhibition may be caused by steric hindrance rather than by direct competition, since the binding sites of AP-1 and Sp-1 are separated by approximately 30 bp. Sp proteins may dominate because of their higher amount/anity than AP-1, since we found that Sp-3 also binds to the Sp-1 site and since it is reported that Sp-3 may regulate gene expression in a positive as well as negative manner (Jiang et al, 1997). It is possible that Ap-1 binding dampens the negative eects of Sp-3 and further induces c-met gene expression.…”
Section: Resultsmentioning
confidence: 84%
“…Ctr, mRNA in untreated cells maintained in culture medium for 24 h. cells. Sp1 and Sp3, like other members of the Sp family, recognize the G ϩ C-rich repeats (47) and act as positive transcription factors on a wide variety of cellular genes (48), including collagen genes (49 -51).…”
Section: Discussionmentioning
confidence: 99%